The Implementation of Anti-Corruption Character Education Through Bali Local Wisdom in Junior High Schools - Sriartha, Putu; Yasmiati, Ni Luh Wayan; Lasmawan, I Wayan (Jurnal Pendidikan Indonesia, 2021)
This study aims to evaluate anti-corruption character education through Balinese local wisdom in junior high schools and formulate strategies to strengthen its implementation. The research samples were determined purposively. The evaluation model used was the CIPPO model (Context, Input, Process, Output, Outcome), modified from the CIPP model. Data were collected by interview, observation, and documentation methods. Data analysis was carried out using quantitative descriptive methods and SWOT analysis. The results showed that the implementation of anti-corruption character education was considered effective with an achievement of 76.06%. The highest achievement is on the input variable of 81.75% (very effective), and the lowest is on the process variable of 61.75% (less effective). The process of implementing anti-corruption education through learning, habituation, and civilizing is still dominant at the theoretical level, not involving students actively and critically in real life. The SWOT analysis resulted in five strategy formulations, namely: (1) establishment of a character education development unit (anti-corruption), (2) transformation of anti-corruption education learning, (3) exemplary, habituation and civilizing, (4) strengthening extracurricular programs, and (5) building cooperation network.